Efektivitas Pengunaan Media Misteri Box Terhadap Hasil Belajar Peserta Didik - permana, Regina Permana Putri; Apriany Lestari, Myrna; Hermawati, Eli (Scientific Exploration: Journal of Indonesian Academic Research, 2025)
This research is motivated by the low learning outcomes of students in the subject of science in class V of SD Negeri 17 Kuningan. This is because the method of delivering the material still uses conventional methods and the lack of use of learning media. The purpose of this study was to determine whether there are differences and improvements in student learning outcomes in the subject of science between classes that use mystery box learning media and classes that use textbooks. This study uses a quasi-experimental method with a Nonequivalent Control Group Design research design. The subjects in this study were 46 students in class V of SD Negeri 17 Kuningan consisting of 23 students in class VA and 23 students in class VC. The data collection technique used a written test in the form of multiple choices. The data obtained were then analyzed using the t-test and N-Gain test. The results of the t-test calculation obtained a value of t count = 8.54 and table = 1.68 (t count > table). So it can be concluded that Hı is accepted and Ho is rejected. This shows that there are differences in student learning outcomes in classes that use mystery box media and classes that use textbooks.The N-Gain calculation shows that the results in the experimental class are 0.5 and the control class is 0.01. So it can be concluded that there is a difference in the increase in student learning outcomes in classes that use mystery box media with classes that use textbooks.